AB0347 Barriers to Achieving Controlled Rheumatoid Arthritis in the Uae. (10th June 2014) - Moufarrej, M.; Mahfoud, Z.; Daoud, J.R.; Badsha, H.
Abstract : Background: Achieving a low DAS28 (disease activity score) of less than 3.2, is a common treatment goal for Rheumatoid Arthritis (RA). In clinics however, despite efforts, some patients still fail to reach treatment goals due to various barriers. Given the relatively high average disease activity level in the UAE with an average DAS28 of 4.3 (1), better understanding the barriers that exist in local clinics may yield novel information regarding how to better treat RA in the future. Objectives: This study aims to better understand the factors that affect low disease activity (DAS28<3.2, LDA) and barriers in the UAE and propose a future course of action in order to improve the treatment of RA within the region. Methods: Data was collected through chart reviews of 182 consecutive RA patients who were seen in a private clinic in Dubai over a 2-month period. Demographic/treatment data and DAS28 scores were collected. Patients were separated into a LDA group and a group comprised of moderate (DAS28 >3.2 and <5.1) and high disease activity (DAS 28 >5.1) (MHDA). We then examined variables that may be associated with LDA and re-examined the MHDA group for barriers such as irreversible joint damage, inability to pay for treatment, resistant disease, patient driven preferences, safety concerns and comorbidities. Results: While 97 (53%) of the 182 patients had achieved the treatment target of DAS 28 <3.2, 21 (11.50%) had high disease activity and 64 (35%) had moderate disease activity. No substantial difference was found in delay to diagnosis, past methotrexate use, or rheumatoid factor or anti-CCP status between the LDA and MHDA group (Table 1 ). However, a significantly larger portion of LDA patients had been previously treated with sulfasalazine, SSA, (36 in LDA vs 14 in MHDA, P0.002) or were presently on biological treatments (24 vs 9, P0.013). For the 85 MHDA patients, 40 (22% of 182) exhibited resistant disease with 25 (13.7% of 182) failing their current first tier disease modifying anti-rheumatic drug (DMARD) treatment or combinations and 15 (8.2% of 182) failing current anti-TNF or biologic treatment. Notably 16 of the 25 failing DMARD treatment (40%) did not change treatment plans due to insufficient insurance. Other notable barriers were patient driven preferences (20%), non-inflammatory musculoskeletal pain (9%), and safety concerns (7%). Conclusions: Over half the patients achieved the DAS28 LDA target. Factors that significantly influenced LDA were prior SSA use and current biological therapy. Among those who did not achieve target (MHDA), the most prominent barriers included resistant disease (47%) and patient driven preferences (20%). Reasons listed for resistant disease and patient-driven preference were primarily socio-economic with 40% of the resistant disease group unable to afford biological drugs and 59% of the patient-driven preference group discontinuing or refusing DMARDs against professional advice. Going forward, better educating patients on the proper use of anti-rheumatic drugs could help reduce the percentage of MHDA patients in the UAE. In addition, a longitudinal study that examines the results of treating the resistant disease group with biologicals would be of key interest. References: Sokka T et al. (2009) Women, men, and rheumatoid arthritis: analyses of disease activity, disease characteristics, and treatments in the QUEST-RA study. Arthritis Res Ther 11: R7. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4275